ANALISIS PERBANDINGAN REAL TIME STREAMING PROTOCOL (RTSP) DAN HYPERTEXT TRANSFER PROTOCOL (HTTP) PADA LAYANAN LIVE VIDEO STREAMING - Ady Nopaldi Rombe; LM Fid Aksara; La Surimi (semanTIK, 2019)
Streaming media is a technology that allows the distribution of audio, video and multimedia data in real time via the internet. One category of streaming media is video streaming. Video streaming is sending digital media in the form of video, sound, and data so that it can be received continuously. Real Time Streaming Protocol (RTSP) is a protocol at the application level that functions to control sending data in real time. RTSP uses and provides an extensible framework to control on-demand data transmissions such as audio and video.HTTP (Hypertext Transfer Protocol) is a protocol for requesting and answering between client and server. An HTTP client such as a web browser usually starts a request by making a TCP/IP connection to a specific port in a remote place (usually port 80). Based on the results obtained from all experiments, it is known that the HTTP protocol is not recommended as a streaming media via the internet because based on the analysis of all tested parameters it has a very high Delay, Packet Loss, and small Throughput, whereas the RTSP from the results of the analysis on all that has been tested has the lowest QoS value.Keywords—Video Live Streaming, Real Time Streaming Protocol (RTSP), Hypertext Transfer Protocol (HTTP)DOI : 10.5281/zenodo.3243149